(untitled) (Ingenieria y Universidad, 2023)
Colombia is a country where a high-temperature climate is predominant. In this type of weather, one of the main damage mechanisms for hot-mix asphalt (HMA) is rutting. Additionally, there are significant efforts being made worldwide in order to attempt to replace natural origin aggregates (NA) that these mixes use, for recycled concrete aggregates (RCA). Because of this, the foregoing study measured stiffness under cyclic load (resilient modulus) and permanent deformation resistance undergo by an HMA mix when the fraction of gravels and sands of an NA is replaced by mass with RCA in proportions of 20, 40, and 80%. Based on the results obtained, it is possible to conclude that using RCA helps to increase HMA rutting resistance in any percentage of analyzed substitution.